Electronic nursing documentation for patient safety, quality of nursing care, and documentation: a systematic review - Wahyuni, Erna Dwi; Nursalam, Nursalam; Dewi, Yulis Setiya; Arifin, Hidayat; Benjamin, Lizy Sonia (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the impact of electronic nursing documentation on patient safety, quality of nursing care and documentation. Method: The systematic review was conducted in December 2022, and comprised a comprehensive search on Scopus, ScienceDirect, ProQuest, PubMed, Cumulative Index to Nursing and Allied Health Literature, Sage Journals and Google Scholar databases for English-language human studies published between 2018 and 2022. The key words used in the search included "Nursing", "care", "documentation", "record", "electronic", "process" and "health services". The risk of bias was assessed using Strengthening the Reporting of Observational Studies in Epidemiology tool. Results: Of the 469 items initially identified, 15(3.2%) were analysed in detail, indicating a positive influence of electronic nursing documentation on patient safety, care quality, and documentation. However, shortcomings were observed in the development of electronic nursing documentation for optimal effectiveness. Conclusion: Electronic nursing documentation significantly enhanced patient safety, care quality and documentation. To facilitate its integration into clinical settings, a standardised and logically structured electronic nursing documentation system is essential. Key Words: Documentation, Electronic health documentation, Nursing, Patient safety, Quality of healthcare.